Genome-Wide Identification and Characterization of Long Non-Coding RNAs in Longissimus dorsi Skeletal Muscle of Shandong Black Cattle and Luxi Cattle - Liu, Ruili; Han, Mingxuan; Liu, Xianxun; Yu, Kun; Bai, Xuejin; Dong, Yajuan (Frontiers in Genetics, 2022)
There is an increasing understanding of the possible regulatory role of long non-coding RNAs (LncRNA). Studies on livestock have mainly focused on the regulation of cell differentiation, fat synthesis, and embryonic development. However, there has been little study of skeletal muscle of domestic animals and the potential role of lncRNA. In this study, the transcriptome numbers of longissimus muscle of different beef cattle (Shandong black catle and Luxi catlle) were used to construct muscle related lncRNAs-miRNA-mRNA interaction network through bioinformatics analysis. This is helpful to clarify the molecular mechanism of bovine muscle development, and can be used to promote animal husbandry and improve animal husbandry production. According to the screening criteria of |FC|≧2 and q < 0.05, a total of 1,415 transcripts (of which 480 were LncRNAs) were differentially expressed (q < 0.05) in the different breeds. Further, we found that the most differentially expressed LncRNAs were found on chromosome 9, in which the differentially expressed LncRNAs targeted 1,164 protein coding genes (MYORG, Wnt4, PAK1, ADCY7,etc) (upstream and downstream<50 Kb). In addition, Pearson’s correlation coefficients of co-expression levels indicated a potential trans regulatory relationship between the differentially expressed LncRNAs and 43844 mRNAs (r > 0.9). The identified co-expressed mRNAs (MYORG, Dll1, EFNB2, SOX6, MYOCD, and MYLK3) are related to the formation of muscle structure, and enriched in muscle system process, strained muscle cell differentiation, muscle cell development, striated muscle tissue development, calcium signaling, and AMPK signaling. Additionally, we also found that some LncRNAs (LOC112444238, LOC101903367, LOC104975788, LOC112441863, LOC112449549, and LOC101907194) may interact with miRNAs related to cattle muscle growth and development. Based on this, we constructed a LncRNAs-miRNA-mRNA interaction network as the putative basis for biological regulation in cattle skeletal muscle. Interestingly, a candidate differential LncRNA (LOC104975788) and a protein-coding gene (Pax7) contain miR-133a binding sites and binding was confirmed by luciferase reporter assay. LOC104975788 may combined miR-133a competitively with Pax7, thus relieving the inhibitory effect of miR-133a on Pax7 to regulate skeletal muscle development. These results will provide the theoretical basis for further study of LncRNA regulation and activity in different cattle breeds.